GATA3 mutations found in breast cancers may be associated with aberrant nuclear localization, reduced transactivation and cell invasiveness. - Gaynor, K; Grigorieva, I; Allen, MD; Esapa, C; Head, R; Gopinath, P; Christie, P; Nesbit, M; Jones, J; Thakker, R (2013)
Somatic and germline mutations in the dual zinc-finger transcription factor GATA3 are associated with breast cancers expressing the estrogen receptor (ER) and the autosomal dominant hypoparathyroidism-deafness-renal dysplasia syndrome, respectively. To elucidate the role of GATA3 in breast tumorigenesis, we investigated 40 breast cancers that expressed ER, for GATA3 mutations. Six different heterozygous GATA3 somatic mutations were identified in eight tumors, and these consisted of: a frameshifting deletion/insertion (944_945delGGinsAGC), an in-frame deletion of a key arginine residue (991_993delAGG), a seven-nucleotide frameshifting insertion (991_992insTGGAGGA), a frameshifting deletion (1196_1197delGA), and two frameshifting single nucleotide insertions (1224_1225insG found in three tumors and 1224_1225insA). Five of the eight mutations occurred in tumors that retained GATA3 immunostaining, indicating that absence of GATA3 immunostaining is an unreliable predictor of the presence of GATA3 mutations. Luciferase reporter assays, electrophoretic mobility shift assays, immunofluorescence, invasion and proliferation assays demonstrated that the GATA3 mutations resulted in loss (or reduction) of DNA binding, decrease in transactivational activity, and alterations in invasiveness but not proliferation. The 991_992insTGGAGGA (Arg330 frameshift) mutation led to a loss of nuclear localization, yet the 991_993delAGG (Arg330deletion) retained nuclear localization. Investigation of the putative nuclear localization signal (NLS) sites showed that the NLS of GATA3 does not conform to either a classical mono- or bi-partite signal, but contains multiple cooperative NLS elements residing around the N-terminal zinc-finger which comprises residues 264-288. Thus, approximately 20 % ER-positive breast cancers have somatic GATA3 mutations that lead to a loss of GATA3 transactivation activity and altered cell invasiveness.